Economical, Constructional, and Cultural Conditions of the ‎Mongols - Rajaa Azeez Shallal; Abdulsattar Mutlag Darweesh (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The current study aimed to investigate the economic, construction, and ‎cultural conditions in Mongolian society by highlighting the natural resources, ‎agricultural, and animal wealth possessed by the Mongolian lands. It also ‎aimed to analyze their impact on lifestyles and social organizations. It also seeks ‎to address commercial activity and architectural aspects, focusing on what is ‎mentioned in historical sources about these aspects. Methodology: The ‎descriptive-analytical approach was adopted, based on studying historical ‎narratives and texts that dealt with Mongolian society at its various stages, ‎analyzing the content of what was mentioned therein regarding economic, ‎constructions, and cultural aspects, and linking them to the nature of the ‎geographical environment and the social structure of that society. Results: The ‎study showed that the Mongolian lands were rich in natural resources, which ‎contributed to the limited development of agricultural wealth, while livestock ‎wealth formed the economic basis of a nomadic society based on migration. It ‎also demonstrated the weakness of industrial activity due to the Mongol tribes' ‎preoccupation with wars and conquests, with a growing interest in trade, ‎especially during the reign of Genghis Khan. On the other hand, architecture ‎was limited in terms of documentation and sources, but the geographical ‎expansion contributed to the Mongols' openness to multiple urban patterns. ‎Conclusions: It can be concluded that the nomadic and military nature of ‎Mongol society influenced the features of its economic and urban ‎development, with the military nature dominating production, and a lifestyle ‎based on herding and trade emerging. Furthermore, the scarcity of historical ‎sources on architecture reflects the absence of a stable urban structure in the ‎early stages, calling for further research in this area to clarify the mutual cultural ‎influences between the Mongols and the peoples they subjugated.‎